PERANAN BRIGADE MOBIL DALAM MEMPERTAHANKAN KEMERDEKANAN INDONESIA PADA PERTEMPURAN BENTENG HURABA TAPANULI SELATAN 1949 - Machmul Alamsyah Harahap; Bedriati Ibrahim; Ahmal Ahmal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The Mobile Brigade was originally a special police force during the Japanese occupation named Tokubetsu Kaisatsu Tai. The purpose of this study (1) to determine the background of the formation of the Mobile Brigade in South Tapanuli (2) to determine the role of the Mobile Brigade in defending Indonesian independence during the battle of Fort Huraba Tapanuli Selatan 1949 (3) to determine the end of the struggle of the Mobile Brigade in defending Indonesian independence in combat Huraba Fort Tapanuli Selatan 1949. This research uses historical methods. The result of the research is that the formation of the Mobile Brigade in Tapanuli was initiated by a member of Tokobetsu Kaisatsu Tai named Mas Kadiran who has the rank of junsha butyo (police commander). The commander of sector I Sub-Territory VII of South Tapanuli / East Sumatra / Asahan / Labuhan Batu appointed Mas Kadiri, commander of the Mobile Brigade as the defense commander at Fort Huraba. In the battle of Fort Huraba on May 5, 1949, 27 people were killed. After the battle of Fort Huraba on May 5, 1949, until the ceasefire in August 1949, the Dutch never made another attack on Fort Huraba.Key Words: Mobile Brigade Independence, Fort Huraba